Threats in production of coriander (Coriandrum sativum) in Andhra Pradesh - Giridhar Kalidasu, C Sarada, (Journal of Spices and Aromatic Crops, 2008)
Andhra Pradesh ranks first in the southern states of the country in production andproductivity of coriander and ranks second in country. Coriander is cultivated in nearly31298 hectares in Andhra Pradesh with a production of 37548 metric tonnes. The productivityof the crop increased from 275 kg/ha in 1990 to 1200 kg/ha by 2005-06. The reduction in cropcoverage has become a serious concern for the department of horticulture and as well asfarmers. The major factors that affected the shift were cultivation of alternate crops andchanging cropping patterns, vagaries in climate, non-availability of quality seed, terminalmoisture stress and fluctuations in market prices. This study also focuses on achievements ofthe state in crossing the average national productivity of the crop through strong researchby AICRP on Spices and efforts of Department of Horticulture in extension programmes.